LEGAL FRAMEWORK FOR THE PROTECTION OF THE FAMILY HOME WITH A SPECIAL FOCUS ON FRENCH LEGISLATION - Plamenac, Jelena (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The legal system of the Republic of Serbia does not contain specific rules regulating the protection of the family home. This paper examines, through a comparative legal analysis, whether it would be desirable to incorporate provisions related to the special protection of the family home into domestic legislation or whether the existing provisions are sufficient to ensure that this legal institution is substantively protected. Special attention is given to solutions found in French legislation, where the protection of this legal institution is highly developed. The main motivation for choosing this topic lies in the fact that in 2023 the family law of the Republic of Srpska introduced the protection of the family home as a distinct institution of family law, making the Republic of Srpska a pioneer in the region in terms of providing special protection for the family home.